Early interaction, infant self-regulation and attachment : a longitudinal study during the first year of life - Barbosa, Miguel Marques da Gama, 1982- (2018)
Tese de doutoramento, Psicologia (Psicologia do Desenvolvimento), Universidade de Lisboa, Faculdade de Psicologia, 2017